High on treatment platelet reactivity against aspirin by non-steroidal anti-inflammatory drugs – pharmacological mechanisms and clinical relevance - Hohlfeld, Thomas; Saxena, Aaruni; Schrör, Karsten (Thrombosis and Haemostasis, 2013)
Inhibition of platelet function by aspirin results from irreversible inhibition of platelet cyclooxygenase (COX)-1. While sufficient inhibition is obtained at antiplatelet doses (75–325 mg/day) in most (≥95%) treated patients, the antiplatelet effect of aspirin and subsequent cardiovascular risk reduction is much less in clinical settings and disease-dependent. Several reasons for this “high on treatment platelet reactivity” are known. This paper reviews the evidence for an interaction between aspirin and other COX inhibitors, namely non-steroidal antiinflammatory drugs (NSAIDs). Numerous experimental studies demonstrated a pharmacodynamic interaction between aspirin and NSAIDs. This likely occurs within the hydrophobic substrate channel of platelet COX-1 and might be explained by molecular competition between inhibitor drugs and substrate (arachidonic acid) at overlapping binding sites. This interaction is found with some compounds, notably ibuprofen and dipyrone (metamizole), but not with others, such as diclofenac and acetaminophen (paracetamol). Hence, this interaction is not a class effect of NSAIDs and/or non-steroidal analgesics but rather due to specific structural requirements which still remain to be defined. In vivo studies on healthy subjects and patients tend to confirm this type of interaction as well as large differences between NSAIDs and non-steroidal analgesics, respectively. These interactions may be clinically relevant and may increase the cardiovascular risk in long-term treatment for primary and secondary cardiovascular prevention in patients with chronic inflammation, such as rheumatoid arthritis. These patients have an elevated risk for myocardial infarctions and may require chronic antiplatelet treatment by aspirin in addition to treatment of inflammatory pain.
Keywords: Aspirin; drug-interaction; non-steroidal anti-inflammatory drugs; dipyrone; platelet function